The Application of K-Means Clustering Method for Rubber Price Grouping in Sengkuang Jaya Village Bengkulu Province - Khairullah Khairullah; Muhammad Husni Rifqo; Harry Witriyono; Adelia Karolina (Jurnal Komputer, Informasi dan Teknologi, 2022)
Sengkuang Jaya village is an area located in Bengkulu province. The calculation of price for rubber is still calculated manually in the village. This study wants to apply the k-means clustering method for calculating rubber prices according to the quality of rubber owned by farmers in Sengkuang Jaya Village, Bengkulu Province. This study aimed to determine prices based on rubber quality in Sengkuang Jaya Village,Bengkulu Province. The tehnique of collecting the data of this study used interview and observation.The results showed that from 15 samples of rubber latex data taken,the price of rubber with the highest cluster was found for rubber 2 weeks and over and for rubber 2 weeks down including cluster 2.The results of testing the rapidminer tools run well without any errors. Base on the result of the study can be suggested that further research can be developed with the same type of data but using better methods such as using the Fuzzy C-Means algorithm, Hard C-Means and completing the sample which may be up to 1 year of rubber storage.